Genetic diversity assessment for the vulnerable migratory cownose ray Rhinoptera bonasus (Myliobatiformes: Rhinopteridae) from the southwestern Atlantic Ocean - Souza, Bruno C. [UNESP] (2021)
Rhinoptera bonasus is a bento-pelagic and highly migratory species occurring from southern United States to northern Argentina. Due to overfishing effects, R. bonasus is currently at risk, classified by the IUCN Red List as vulnerable. Considering the lack of molecular data available for R. bonasus, this study aimed to describe the genetic variability and population structure of specimens sampled from three Brazilian coast ecoregions (Amazon ecoregion, Para; Northeastern ecoregion, Pernambuco and Southeastern ecoregion, Rio de Janeiro, Sao Paulo and Santa Catarina), through five polymorphic microsatellite markers. Here testing the panmixia hypothesis for Brazilian ecoregions and test natal philopathy. A total of 69 analyzed specimens revealed individual and significant genetic differentiation between the sampled locations. Phi(ST) (0.12), PCA, DAPC and Bayesian analyses of the genetic population structure revealed at least two distinct genetic R. bonasus groupings. IBD tests were significant, indicating a correlation between genetic and geographical distance among populations, which can be explained by reproductive philopatric behavior. Philopatric behavior associated with R. bonasus mobility may influence the differentiation values observed for all loci in the investigated samples.